Response of corn (Zea Mays) to combinations of plantgrowth-promoting rhizobacterial inoculants - Gentapan, Karla May C. (2009)
The response of corn in sterile and nonsterile sandy loam soil amended with rhizobacterial isolates and combinations thereof were determined within a 17-week period. Growth response was assessed based on shoot length, rate of leaf emergence, leaf color rating, cob yield, and shoot and root fresh and dry weight. Corn plants inoculated with Rh2-MS-CO (identified as Beijerinckia mobilis) and grown in sterile soil exhibited the highest rate if increase in shoot length (8.86 cm/3 days) and final shoot length (197.61 cm). this treatment also exhibited high cob mass (37.70 g), shoot by weight (21.26 g) and root dry weight (2.44 g). higher leaf color ratings were obtained in treatments grown in sterile soil as compared to treatments grown in nonsterile soil. Higher values were also obtained in the growth parameters of bacteria-amended treatments as compared to the control groups. The highest total heterotrophic count was obtained from nonsterile soils, while the highest nitrogen-fixing bacterial counts were obtained from sterile soils specifically the treatment amended with Rh2-MS-CO and the combination of Rh1-MS-CO and Rh3-MS-CO. the results indicate that rhizobacterial inoculants introduced may have contributed to the growth and development of corn plants. The poor results from treatments in nonsterile soil may have resulted from bacterial competition leading to antagonism and inhibition. The heterotrophic and nitrogen-fixing bacterial counts also suggest that sterile soils allow for better proliferation of the population of the introduced nitrogen-fixers. Also, a high population